The Impact of Supervision Process toward Counselling Competencies among Malaysian Trainee Counsellors - Suhaili, Arifin; Noor Syamilah, Zakaria; Wan Marzuki, Wan Jaafar; Nor Mazlina, Ghazali; Nor Shakira, Sakari (IAFOR publishing, 2023)
The main objective of this study is to investigate the level of counselling competencies among trainee counsellors in supervision. It also aims to analyze the relationship between frequency of supervisions with counselling competencies. This study was conducted among trainee counsellors (counselling students) from nine public universities all across Malaysia that offer bachelor programmes in counselling. The respondents consisted of n=204 trainee counsellors and n=62 lecturer supervisors who were selected in pairs using stratified random sampling. The Counselling Competencies Scale was used to assess the counselling competencies of trainee counsellors. The results of the study revealed that most of the respondents were at the “meets expectations” level of the counselling competency. The results also showed that there was a significant relationship between the frequency of supervisions with two sub-scales of counselling competency, namely professional behaviour (d=.180, p<.009) and counselling skills (d=.169, p<.019). This research finding has implications for the training field of counselling education in Malaysia. Additional research on other areas, such as the other contribution factors toward the trainee counsellor’s competency is needed for future studies.